DCLRE1B as a novel prognostic biomarker associated with immune infiltration: a pancancer analysis - Mi Zou; Zuxi Feng; Kaibo Hu; Yuan Shu; Ting Li; Xiaogang Peng; Leifeng Chen; Leyang Xiao; Shouhua Zhang; Ting Xiong; Xueqiang Deng; Jie Peng; et al. (Scientific Reports)
Abstract The DNA cross-link repair 1B (DCLRE1B) gene is involved in repairing cross-links between DNA strands, including those associated with Hoyeraal–Hreidarsson syndrome and congenital dyskeratosis. However, its role in tumours is not well understood. DCLRE1B expression profiles were examined in tumour tissues and normal tissues using TCGA, GTEx, and TARGET datasets. Additionally, we performed experiments with clinical melanoma samples to verify DCLRE1B expression patterns. We also performed pancancer analyses to investigate the diverse roles of DCLRE1B in the biological functions of various cancers. DCLRE1B exhibited distinct expression patterns and played crucial prognostic roles in most tumours. In particular, high expression of DCLRE1B in melanoma was significantly correlated with a poor prognosis and increased malignancy. DCLRE1B was also found to be associated with the immune landscape and various immune biomarkers and regulators. Furthermore, our analysis identified potential small molecules that could target DCLRE1B in different cancer types. The DCLRE1B gene may be involved in the development and occurrence of a variety of cancers. Additionally, DCLRE1B affects various tumour types not only by mediating DNA repair but also by shaping the differential immune microenvironment. In conclusion, our research offers fresh perspectives on the diagnosis and treatment of different types of cancers.